Glycemic Response to Two Doses of Resistant Starch Type 4: A Randomized Controlled Crossover Trial (P08-091-19). (24th October 2019) - Steele, Trevor; Maningat, Clodualdo; Seib, Paul; Haub, Mark; Rosenkranz, Sara
Abstract: Objectives: Resistant starches (RS) have a beneficial effect on glucose and insulin responses in the postprandial period following carbohydrate (CHO) consumption. In comparison to resistant starch types 1–3, there is little evidence investigating the effects of resistant starch type 4 (RS4) on these metabolic responses. The primary aim of the current study was to determine whether the glycemic response to a nutritional RS4 bar (RS4) was different compared to a puffed wheat bar (PWB), provided at the standard testing amount of 50 g available CHO and a lower dose of 30 g available CHO, thereby investigating a dose-response effect. Methods: Apparently healthy adults ( n  = 15; 26.1 ± 4.8yrs) participated in this controlled randomized crossover trial. All participants completed six trials: 50 g dextrose control drink (50DEX), 30 g dextrose control drink (30DEX); and nutrition bars containing: 50 g available CHO of PWB or RS4 (50PWB; 50RS4), and 30 g available CHO PWB or RS4 (30PWB; 30RS4). Participants fasted for 10–12 hrs prior to each visit with a minimum 72hr washout period between trials. Blood glucose was measured via LDX Cholestech at baseline and 10, 20, 30, 60, 90, and 120 min post consumption. Primary outcomes were determined using mixed-effects models in GraphPad Prism 8.0.1. Results: Glucose incremental area under the curve (iAUC) was not significantly different between the 50 g conditions ( P  = 0.054). However, peak blood glucose was significantly lower in the 50RS4 condition compared to 50PWB and 50CON ( P  = 0.027; P  = 0.004 respectively); and there was no difference between 50PWB and 50CON ( P  = 0.496). While 30RS4 and 30PWB glucose iAUCs were lower compared to 30CON ( P  = 0.002), there was no difference between 30RS4 and 30PWB ( P  = 0.48). Peak blood glucose was reduced for both 30PWB and 30RS4 when compared to 30CON ( P  = 0.005; P  =  0 .002 respectively), with no difference between 30 g CHO bars ( P  = 0.22). Conclusions: These results indicate a potential dose-response effect for RS4 on postprandial glycemia. Specifically, at the 50 g available CHO standard testing amount, RS4 reduced peak blood glucose as compared to the 50PWB control. At the lower dose of available CHO, there was not a statistically significant beneficial effect for 30RS4 on postprandial glycemia. There may be a potential floor effect where RS4 has no further benefit when available CHO is low. Funding Sources: MGP Ingredients Inc.